2017
DOI: 10.18869/acadpub.jafm.73.239.27027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Horizontal Magnetic Field and Horizontal Rotation on Thermosolutal Stability of a Dusty Couple-Stress Fluid through a Porous Medium: a Brinkman Model

Abstract: The problem of the onset of double diffusive convection in a couple-stress fluid saturated with a porous medium is studied under the effects of magnetic field, rotation and suspended dust particles. Linear stability analysis based on the method of perturbations of infinitesimal amplitude is performed using the normal mode technique for the case of free-free boundaries. The governing hydrodynamic and hydromagnetic equations of fluid flow are governed by the Brinkman model. The stability analysis examines the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…A compressible couple-stress fluid layer with suspended particles in a porous medium was examined by Sunilet et al [7] who found that suspended particles had a destabilizing effect on the system. Stanly and Vasanthakumari [8] investigated the thermal instability of a dusty couple-stress fluid in the presence of rotation and magnetic field. Kumar et al [9], Sharma and Thakur [10], Sunilet et al [11], Mishra and Kumar [12] also studied the effect of different fields on a couple-stress fluid.…”
Section: Introductionmentioning
confidence: 99%
“…A compressible couple-stress fluid layer with suspended particles in a porous medium was examined by Sunilet et al [7] who found that suspended particles had a destabilizing effect on the system. Stanly and Vasanthakumari [8] investigated the thermal instability of a dusty couple-stress fluid in the presence of rotation and magnetic field. Kumar et al [9], Sharma and Thakur [10], Sunilet et al [11], Mishra and Kumar [12] also studied the effect of different fields on a couple-stress fluid.…”
Section: Introductionmentioning
confidence: 99%
“…On applying uniform vertical rotation and uniform vertical magnetic field (Kumar, 2012) has studied thermosolutal convection in a couple stress fluid layer heated and soluted from below and found stable solute gradient and rotation has stabilizing effect. (Kumar et al, 2017) investigate the start of double diffusive convection in a pair stress fluid saturated with a porous material under the influence of a magnetic field, rotation, and suspended particles. (Kumar et al, 2009) investigated thermosolutal instability of a couple stress spinning fluid in the presence of a magnetic field and discovered that oscillatory modes are introduced owing to the existence of rotation, a magnetic field, and a solute gradient.…”
Section: Introductionmentioning
confidence: 99%